Implementation of Pregnancy Exercises on Mothers' Readiness in Facing the Childbirth Process - Khusnul Nikmah; Ida Susila (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Pregnancy exercise is a sports activity carried out by pregnant women to prepare themselves for the birth process. Pregnancy exercise is given to pregnant women to prepare the mother's physical condition, to maintain the condition of the muscles and joints which play a role in the birth process, as well as to prepare the mother's psychological condition, especially to foster confidence and self-readiness in facing the birth process, so pregnancy exercise really needs to be emphasized to pregnant women. Pregnancy exercise is very important for pregnant women from 22 weeks of gestation onwards. The research design carried out was Correlational Analysis.